2020
DOI: 10.1002/smll.202003969
|View full text |Cite
|
Sign up to set email alerts
|

Improved Stability and Photothermal Performance of Polydopamine‐Modified Fe3O4 Nanocomposites for Highly Efficient Magnetic Resonance Imaging‐Guided Photothermal Therapy

Abstract: Magnetic nanomaterials are a promising class of contrast agents for magnetic resonance imaging (MRI). However, their poor stability and low relaxivity are major challenges hindering their clinical applications. In this study, magnetic theranostic nanoagents based on polydopamine‐modified Fe3O4 (Fe3O4@PDA) nanocomposites are fabricated for MRI‐guided photothermal therapy (PTT) cancer treatments. Their high transverse relaxivity of 337.8 mM−1 s−1 makes these Fe3O4@PDA nanocomposites a promising T2‐weighted MRI c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 50 publications
2
75
0
Order By: Relevance
“…The presence of N element was derived from PDA, indicating the successful formation of PDA coating on the surface of Cu‐GA‐CA‐PDA NRs. [ 23 ] In addition, the XPS analysis revealed that there were three strong Cu 2+ satellites at 962.17, 943.47, and 940.17 eV in the Cu 2p spectra of Cu‐GA‐CA NSs and Cu‐GA‐CA‐PDA NRs, which were similar to some previous reports. [ 24 ] The peaks at 954.07 and 934.17 could be assigned to Cu 2p 1/2 and Cu 2p 3/2 , respectively (Figure 3i).…”
Section: Resultssupporting
confidence: 85%
“…The presence of N element was derived from PDA, indicating the successful formation of PDA coating on the surface of Cu‐GA‐CA‐PDA NRs. [ 23 ] In addition, the XPS analysis revealed that there were three strong Cu 2+ satellites at 962.17, 943.47, and 940.17 eV in the Cu 2p spectra of Cu‐GA‐CA NSs and Cu‐GA‐CA‐PDA NRs, which were similar to some previous reports. [ 24 ] The peaks at 954.07 and 934.17 could be assigned to Cu 2p 1/2 and Cu 2p 3/2 , respectively (Figure 3i).…”
Section: Resultssupporting
confidence: 85%
“…Chemical functions charged at pH 7.4 (amine, carboxylic acid) and polymer PEG chains bring electrostatic and steric repulsions ensuring high colloidal stability in biological media [ 10 ] Moreover, another advantage of a silica layer is to limit dipolar interactions between the magnetic particles [ 11 ]. Polydopamine coating is an alternative strategy also studied, showing promising results, notably to combine magnetic resonance imaging and photothermal therapy, due to the good photothermal effect of polydopamine [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) has been demonstrated as a powerful technique for the visualization of the anatomical structure with high spatial resolution [1][2][3]. Compared with computed tomography (CT) [4], positron emission tomography (PET), and single photon emission computed tomography (SPECT) [5], MRI offers several advantages including excellent soft-tissue contrast, the absence of potentially destructive ionizing radiation, and multi-functional imaging with diverse applications [6][7][8].…”
Section: Introductionmentioning
confidence: 99%